Kebutuhan sosial-emosional anak tunagrahita berbakat dan implikasinya bagi pendidikan inklusif - Nisa, Layli Wahidati Aminun (Maliki Interdisciplinary Journal, 2026)
Gifted children with intellectual disabilities, or twice-exceptional children, are individuals who have intellectual disabilities as well as extraordinary potential in certain fields. This dual profile creates complex educational needs, especially in the socio-emotional aspect, which is often overlooked. This study aims to describe the socio-emotional needs of gifted children with intellectual disabilities and formulate the implications for inclusive education. The study was conducted using a qualitative approach with a subject, a teenager with the initials D, who is gifted in information technology and sports but experiences challenges in social interaction. The results of the study show that D experiences positive social-emotional development when in a supportive, adaptive learning environment that values his individual potential. The role of teachers is very important in supporting this success through a strength-based approach and providing space for self-actualization. These findings indicate that inclusive education must integrate academic and social-emotional aspects in a balanced manner so that gifted children with intellectual disabilities can develop optimally. Collaboration between schools, teachers, and families is needed to create an environment that is responsive to the unique needs of these children with dual exceptionalities.